Corporate Characteristics and Carbon Disclosure: Evidence from Indonesia’s Non-Cyclical Consumer Sector - Kurniawati, Kurniawati; Maria, Maria (PT FORMOSA CENDEKIA GLOBAL, 2025)
Rising global dan local demands for corporate environmental accountability, revealing carbon emissions has emerged as a crucial element of transparency and sustainable practices. This study aims to analyze the influence of internal company characteristics that consist of company size, profitability, leverage and environmental management systems influence carbon emission disclosure within non-cyclical consumer sector firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. By purposive sampling selected 110 data samples during 2020-2022. Multiple linear regression analysis was used to test the hypothesis with the help of SPSS software. The results showed that company size and environmental management systems positively affect carbon emission disclosure, while leverage negatively affect carbon emission disclosure. Surprisingly profitability has no effect on carbon emission disclosure. This indicates that environmental responsibility awareness is higher in larger companies and has implemented ISO 140001.